Development and verification of a combined immune- and cancer-associated fibroblast related prognostic signature for colon adenocarcinoma - Wei, Jingsun; Ge, Xiaoxu; Qian, Yucheng; Jiang, Kai; Chen, Xin; Lu, Wei; Yang, Hang; Fu, Dongliang; Fang, Yimin; Zhou, Xinyi; Xiao, Qian; Tang, Yang; et al. (Frontiers in Immunology, 2024)
To better understand the role of immune escape and cancer-associated fibroblasts (CAFs) in colon adenocarcinoma (COAD), an integrative analysis of the tumor microenvironment was performed using a set of 12 immune-and CAF-related genes (ICRGs). Univariate and least absolute shrinkage and selection operator (LASSO) Cox regression analyses were used to establish a prognostic signature based on the expression of these 12 genes (SIPR5, AEN, IL20RB, FGF9, OSBPL1A, HSF4, PCAT6, FABP4, KIF15, ZNF792, CD1B and GLP2R). This signature was validated in both internal and external cohorts and was found to have a higher C-index than previous COAD signatures, confirming its robustness and reliability. To make use of this signature in clinical settings, a nomogram incorporating ICRG signatures and key clinical parameters, such as age and T stage, was developed. This nomogram showed slightly better predictive accuracy than the ICRG signature alone, as indicated by the areas under the receiver operating characteristic curves. The relationships between risk scores (RS) based on the expression of the ICRGs and other key immunotherapy variables, such as immune checkpoint expression, immunophenoscore (IPS), and microsatellite instability (MSI), were also evaluated. Consideration of all of these variables together resulted in more accurate prediction of treatment efficacy, enabling personalized immunotherapy for patients with COAD. These findings indicate that the ICRG signature may be a valuable tool for predicting prognostic risk, evaluating the efficacy of immunotherapy, and tailoring personalized treatment options for patients with COAD.